The role of training on smallholder farmers’ adoption of orange-fleshed sweet potato in Ethiopia - Lidya Samuel; Marcia Dutra de Barcellos; Nathaline Onek Aparo; Mulugeta D. Watabaji; Hans De Steur (PLoS ONE, 2026)
Biofortified orange-fleshed sweet potato (OFSP) offers a viable strategy for combating vitamin A deficiency in Sub-Saharan Africa. Despite its nutritional benefits, its adoption among Ethiopian smallholder farmers remains limited. This study investigated the role of training in driving OFSP adoption, using a qualitative experiment grounded in the Theory of Planned Behavior and the Technology Acceptance Model. A total of 65 Ethiopian sweet potato farmers were interviewed before and after training, of which 33 were trained (17 adopters and 16 non-adopters). The findings highlight that training substantially enhanced farmers’ knowledge, improving their cultivation practices and addressing key barriers such as pest control and vine availability. The training also led to a measurable improvement in OFSP yield, indicating its impact not only on behavioral intention but also on actual agronomic outcomes. Perceived ease of use and perceived usefulness emerged as important predictors of adoption behavior, with trained farmers reporting increased confidence in growing OFSP. Additionally, decisions were strongly influenced by subjective norms set by community leaders and peer farmers, underscoring the role of social dynamics in the adoption process. The dissemination of high-quality OFSP vines further supported sustained adoption. The results of this exploratory study suggest that while training is important for improving cultivation techniques, individual motivation and social support also play a key role in farmers’ decision-making. Alongside the qualitative insights, quantitative yield comparisons were incorporated, and the integration of qualitative and quantitative evidence provides valuable insights into how perceptions of benefits, ease of use, and social norms shape adoption behavior, informing strategies to promote wider adoption of biofortified crops. More research is needed to further validate these findings, preferably through larger samples and longitudinal study designs.